ANALYZING CORPORATE JOB MARKET FOR DEVELOPING INFORMATION AND KNOWLEDGE PROFESSIONALS: THE CASE OF A DEVELOPING NATION - Rehman, Sajjad ur (Malaysian Journal of Library and Information Science, 2008)
The paper presents the case of a developing nation—Kuwait—for analyzing its corporate job market for developing and knowledge professionals. The paper is based on the analysis of a body of research that has cumulated over the last 5-6 years. These studies were focused on the status of information management operations in Kuwaiti corporate companies, manpower and organizational issues related to information technology (IT) and information professionals, information management activities of finance companies, and information and knowledge management education. It has been noted that this corporate market is aggressive in pursuing strategic initiatives in employing latest technologies and management approaches. These organizations also appear to be in need of qualified human resources, equipped with befitting competencies, who can assume key managerial and professional roles for information and knowledge positions. There is also a need for creating meaningful partnerships between industry and trade and the higher education institutions, which might be instrumental in designing suitable programmes of education and training in information and knowledge management. Based on these findings, this paper analyses the needs of the corporate job market of Kuwaiti corporate sector for the areas of information and knowledge management. Strategies for developing appropriate competencies have also been outlined.